BAY 81‐8973 demonstrated efficacy, safety and joint status improvement in patients with severe haemophilia A in the LEOPOLD I extension for ≤2 years. (23rd March 2020) - Mahlangu, Johnny; Lopez Fernandez, Maria Fernanda; Santagostino, Elena; Lalezari, Shadan; Tseneklidou‐Stoeter, Despina; Beckmann, Horst; Church, Nikki
Abstract: Objectives: BAY 81‐8973 (Kovaltry ® ), a full‐length, unmodified, recombinant human factor VIII, provided excellent bleeding control for patients with haemophilia A in the pivotal 1‐year LEOPOLD I trial. The LEOPOLD I extension evaluated long‐term efficacy and safety of BAY 81‐8973 prophylaxis. Methods: After completing LEOPOLD I, patients continued receiving 20‒50 IU/kg BAY 81‐8973 two‐ or three‐times weekly in the extension. Outcomes included annualised bleeding rate (ABR) and haemostasis during surgery. Results: Fifty‐five patients aged 12‐65 years participated in the extension. Median (range) exposure days during the 2‐year total study period was 309 (115‐355). No patient switched regimens. Median (Q1; Q3) ABR for all bleeds was 2.0 (1.0; 6.1) during the pivotal study, 2.0 (0.0; 5.2) during the extension, and 2.0 (0.5; 5.5) combined. The proportion of joint bleeds affecting target joints decreased (pivotal study: 90.9%, extension: 60.0%). Haemostasis was assessed as excellent/good in all five major surgeries. One serious adverse event (myocardial infarction) occurred in a patient with cardiovascular risk factors. No patients developed inhibitors. Conclusions: BAY 81‐8973 prophylaxis efficacy outcomes in the pivotal study were maintained or, in the case of joint protection, improved during the extension, with a safety and tolerability profile consistent with previous experience.